Anosov representations with Lipschitz limit set - Pozzetti, Maria Beatrice; Sambarino, Andrés; Wienhard, Anna (Geometry & topology, 2023)
We study Anosov representations whose limit set has intermediate regularity, namely is a Lipschitz submanifold of a flag manifold. We introduce an explicit linear functional, the unstable Jacobian, whose orbit growth rate is integral on this class of representations. We prove that many interesting higher-rank representations, including Θ-positive representations, belong to this class, and establish several applications to rigidity results on the orbit growth rate in the symmetric space.